Beware glowing cadavers: bioluminescence of nematode symbiont Photorhabdus protects nematode-infected host cadavers from nocturnal scavengers - Cassells, Maria D.; Labaude, Sophie; Griffin, Christine T. (Frontiers in Ecology and Evolution, 2024)
Photorhabdus spp. are the only known terrestrial bioluminescent bacteria. We show that the bioluminescence produced by these bacteria reduces scavenging activity on the insect cadavers they colonize. Photorhabdus spp. are the symbiont of the insect pathogenic nematodes Heterorhabditis spp. Together they kill insects and colonize the cadaver. The function of their bioluminescence has been the subject of debate, but here for the first time we demonstrate an ecological benefit. In our experiments, fewer Photorhabdus temperata -infected cadavers than uninfected cadavers were scavenged, but only in dark conditions where their bioluminescence would be visible. This was the case both in the field and in laboratory experiments with Lehmannia valentiana slugs (the primary scavengers found in our field tests). We also show that L. valentiana is innately deterred from scavenging on uninfected cadavers in proximity to light imitating the bioluminescence of Photorhabdus, indicating that luminescence can be a deterrent independent of chemical cues. We propose a multimodal defense where bioluminescence works together with the chemical defenses also produced by Photorhabdus to deter scavengers, such as slugs, from feeding on the host cadaver, with the potential for aposematism.